Evaluation of DMFT Index in the 8-12 Years old Students of Zahedan City, Iran - Foroogh Amirabadi; Edris Bazafshan; Javid Dehghan; Mohammad Ali Zazouli (علوم بهداشتی ایران)
Background and purpose: Dental caries or tooth decay is one of the most important health problems in human life. In addition, tooth decay is an infectious disease that affects all populations Worldwide. The purpose of this study was to determine the decayed, missing and filled teeth (DMFT) index among a representative sample of 8-12 years old school children in Zahedan City, Iran. Materials and Methods: This descriptive and cross-sectional study was performed in 2012-2013 on 1500 (774 girls and 726 boys) 8-12 years old students were randomly selected in Zahedan City (South East of Iran) to assess the DMFT index. The DMFT index was determined using the standard method suggested by World Health Organization (WHO) and data were analyzed using SPSS software (version 18.0) and presented as mean ± standard deviation (SD). Results: It was observed that 43.6% of the individuals had at least one teeth lesion. The mean and SD of DMFT value for all ages was 1.02 ± 1.36. Male children had higher mean DMFT score of 1.01 ± 1.41 compared with 1.00 ± 1.41 for females (P > 0.05). Also, maximum DMFT (1.38 ± 1.62) was observed among students that never seen a dentist per year. Analysis of variance analysis showed that there is not a significant correlation between DMFT index and brushing times. Conclusion: According to the results of this study, the mean DMFT scores in 8-12 years old students are lower than the global standards suggested by WHO.